سياسة الولايات المتحدة الأمريكية تجاه الصراع بين الإمامة والسلطنة في عمان ١٩٥٤ - ١٩٥٩ - علاوي, علي عادل (مجلة مركز بابل للدراسات الانسانية, 2025)
يُعد الصراع بين الإمامة والسلطنة في عُمان 1954-1959 أحد أبرز الصراعات التي شهدتها منطقة الخليج العربي والشرق الأوسط خلال النصف الثاني من القرن العشرين ، إذ تزامن نشوبه مع متغيرات إقليمية ودولية ارتبطت بتصاعد حدة الحرب الباردة التي شهدها العالم بعد نهاية الحرب العالمية الثانية بين المعسكرين الغربي بقيادة الولايات المتحدة الأمريكية والشرقي بقيادة الاتحاد السوفيتي ، وقد كان لتلك المتغيرات أثر واضح في رسم سياسة الولايات المتحدة تجاه الصراع الذي شهده عُمان بين الإمامة والسلطنة ، على الرغم من بروز المصالح النفطية والاقتصادية والمنافسة الشديدة بين شركات النفط البريطانية والأمريكية على امتيازات التنقيب في عُمان وإمارات الخليج الأخرى ، ودورها الكبير في تحديد الموقف الأمريكي بما يتماشى مع تلك المصالح ، إلا أن الولايات المتحدة الأمريكية أعطت الأولوية للمصالح الاستراتيجية بعيدة المدى في كيفية التعامل مع طرفي الصراع في عُمان والجهات الفاعلة فيه ، مع إيجاد توازن في سياستها تجاه حلفائها على الساحتين الإقليمية والدولية ، والأخذ بنظر الاعتبار ضرورة إغلاق أية ثغرة إمام توغل الشيوعية إلى تلك المنطقة الحيوية بالنسبة للمصالح الأمريكية ، وقطع الطريق على الاتحاد السوفيتي الذي كان يطمح في مد نفوذه إلى تلك المنطقة الغنية بالنفط ، وبالتالي إيجاد موطئ قدم له فيها مستغلًا مثل تلك الصراعات ، الأمر الذي يحقق له نصرًا استراتيجيًا في صراعه مع المعسكر الغربي . وعلى هذا الأساس تعاملت الولايات المتحدة الأمريكية مع ذلك الصراع الذي شهدته عُمان خلال تلك المدة التي كانت تعج بالمتغيرات السياسية والعسكرية والتحالفات الإقليمية والدولية في خضم الحرب الباردة ، ونجحت في الحفاظ على مصالحها في المنطقة مع دعم وجود حلفائها وإبقاء الخطر السوفيتي بعيدًا عنها.
Keywords: Relations -- Oman -- Etats-Unis

The American mission hospitals in Oman 1893-1974, 81 years - Bosch, Donald (2000)
Keywords: Médecine -- Oman; Relations -- Oman -- Etats-Unis

العلاقات التجارية الامريكية العمانية (1856-1833) - يوسف, دلال أمير (مجلة دراسات في التاريخ والآثار, 2025)
Keywords: Relations -- Oman -- Etats-Unis

The Sultan of Muscat in Vermont: Reimagining the Middle East in World History - Roberts, Nicholas P. (Middle East Critique, 2025)
While historians have never written about it, in May 1846 the Sultan of Muscat arrived in Weathersfield, Vermont for his first voyage to the United States. This article uses the Sultan’s arrival in Vermont as a platform for augmenting a growing chorus of historians challenging the geographic and disciplinary boundaries that continue to define Middle East Studies. Using archival sources from the US, UK, Zanzibar, and a range of secondary sources, this article addresses a complex centuries-long process of Omani expansion and expropriation that culminated in Zanzibar in the nineteenth century and the height of the Omani Empire as an active participant in shaping the modern world economy. The writing of world history and of Middle East history generally continues to commence from the presupposition of an inevitably ascendant Western-created and led modern world. This article challenges the latter assumption.
Keywords: Relations -- Oman -- Etats-Unis

Breaking the Strategic Glass: The Carter Administration and Oman, 1977–1980 - White, John Bernell, Jr. (Journal of Cold War Studies, 2024)
When Jimmy Carter became the U.S. president in January 1977, the United States and Oman did not have any formal security arrangements, apart from occasional landings of U.S. military aircraft on Oman's Masirah Island. Although Oman's leader, Sultan Qaboos bin Said, hoped to establish closer security ties with the United States, the Carter administration chose to continue President Richard Nixon's policy of relying on the “twin pillars” of Iran and Saudi Arabia to reinforce Western security in the Persian/Arabian Gulf region. Oman remained mostly a strategic afterthought until a series of crises unfolded in the greater Middle East: a Communist coup in Afghanistan in April 1978, the fall of the Shah of Iran in January 1979, and a war between Marxist South Yemen and North Yemen shortly thereafter. In November 1979, Iranian terrorists backed by the Islamic regime stormed the U.S. embassy in Tehran and seized dozens of hostages. This was followed a month later by the Soviet invasion of Afghanistan. With the fall of the Shah and the collapse of the “twin pillars” policy, the Carter administration began a sustained effort to create a Rapid Deployment Force for the Middle East and to gain access to Oman's strategic military facilities. After several months of arduous negotiations, Carter and his team were able to conclude a Facilities Access Agreement with Oman in June 1980, a transformative process that gave Washington the ability to insert U.S. military personnel into the Gulf and Indian Ocean on a contingency basis. The Carter administration's effort stands as a significant achievement, converting Oman into the most reliable U.S. ally in the Gulf region in the 1980s.
Keywords: Relations -- Oman -- Etats-Unis

A historical survey of American-Omani relations: 1790 to the present - Leonard, Douglas R. (The Ibadism of Oman Its Overseas Development and its Perception Overseas, 2011)
Keywords: Relations -- Oman -- Etats-Unis

العميل الأمريكي المنسي .. سلطنة عمان و السلطان كابوس - الصهيل (www.ekhlaas.org, 2008)
Keywords: Relations -- Oman -- Etats-Unis

A Study of the Formative Factors of the Free Trade Agreement Between Oman and the United States - Smith, Gregory (Independent Study Project (ISP) Collection, 2006)
Keywords: Relations -- Oman -- Etats-Unis

Omani-US Relations (1833-1939) - Bahrani, Imad Jasim Al (Liwa : journal of the National Center for Documentation and Research, 2014)
Keywords: Relations -- Oman -- Etats-Unis

Why Has America Overlooked Oman? - Eishen, Jacob (The National Interest, 2018)
The United States would be remiss in damaging relations with this valuable player in the complex Middle East.
Keywords: Relations -- Oman -- Etats-Unis

La politique étrangère des Etats-Unis vis-à-vis d'Oman : La difficulté de l'établissement d'une alliance militaire entre els deux pays de 1975 à 1979 - Shaqsi, Sulaiman al- (Université Laval, 2011)
Keywords: Relations -- Oman -- Etats-Unis

الإرسالية الأميركية في عُمان: قصتها وخِطابُها الديني - الحجري, هلال بن سعيد (التفاهم, 2011)
Keywords: Relations -- Oman -- Etats-Unis

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Etats-Unis